PERBEDAAN BREAST CARE DAN PIJAT OKSITOSINTERHADAP KECUKUPAN ASI PADA IBU NIFAS - Lia Nurwiliani; Marjani Khoirunnisa; Helma Herawati (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Low production of breast milk could interfere with the breastfeeding process. Breast care and oxytocin massage were alternative actions to increase the production of breast milk. A preliminary study conducted at PMB Delima Cimahi showed that there were 6 out of 10 postpartum mothers whose breast milk was not flowing smoothly. The purpose of this study was to determine the difference in the adequacy of breast milk in postpartum mothers who were given breast care vs oxytocin massage. The research method was comparative. Sampling was defined by purposive sampling technique as many as 30 postpartum mothers were divided into two groups. The analytical test used was the chi-square test with the results tests obtained as p-value 0.023 < = (0.05) meaning that there was a difference in the adequacy of breast milk in postpartum mothers who were given breast care vs oxytocin massage. The odds ratio (OR) with a confidence interval of 95% was obtained at 9,750. It was hoped that every postpartum mother can do breast care and oxytocin massage correctly and regularly to support the adequacy of breast milk.